2013
DOI: 10.3389/fnhum.2013.00185
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious motor activation during action perception: beyond correlational evidence

Abstract: Neurophysiological and imaging studies have shown that seeing the actions of other individuals brings about the vicarious activation of motor regions involved in performing the same actions. While this suggests a simulative mechanism mediating the perception of others' actions, one cannot use such evidence to make inferences about the functional significance of vicarious activations. Indeed, a central aim in social neuroscience is to comprehend how vicarious activations allow the understanding of other people'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(114 citation statements)
references
References 148 publications
(175 reference statements)
9
104
0
1
Order By: Relevance
“…Several previous studies have shown that observing others' actions facilitates the observer's motor system (Fadiga et al 2005;Avenanti et al 2013). However, it is unclear whether such facilitation reflects the mapping of low-level action descriptors, as suggested by the match with the observed or inferred pattern of muscle activation in terms of muscle somatotopy and temporal deployment (Gangitano et al 2001;Borroni et al 2005;Urgesi et al 2006;Valchev et al 2015), or the higher-level aspects such as goals (Cattaneo et al 2009(Cattaneo et al , 2013Cavallo et al 2013) and intentions (Tidoni et al 2013), as suggested by the generalization of effects across muscles (Borroni et al 2008) or effectors (Senna et al 2014;Finisguerra et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that observing others' actions facilitates the observer's motor system (Fadiga et al 2005;Avenanti et al 2013). However, it is unclear whether such facilitation reflects the mapping of low-level action descriptors, as suggested by the match with the observed or inferred pattern of muscle activation in terms of muscle somatotopy and temporal deployment (Gangitano et al 2001;Borroni et al 2005;Urgesi et al 2006;Valchev et al 2015), or the higher-level aspects such as goals (Cattaneo et al 2009(Cattaneo et al , 2013Cavallo et al 2013) and intentions (Tidoni et al 2013), as suggested by the generalization of effects across muscles (Borroni et al 2008) or effectors (Senna et al 2014;Finisguerra et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that, at this stage of processing (300 msec), neural activity reflecting motor resonance was stronger in highly empathetic participants who tend to take the psychological perspectives of others in daily life, but was not critical for visual recognition of emotional body postures. These results revealed two distinct functional stages of motor cortex involvement during perception of emotional body language: an initial stage (~150 msec) reflecting increased motor readiness in the left hemisphere and perceptual mechanisms in the right hemisphere, and a later stage (~300 msec) in which the motor cortices bilaterally implement motor resonance, which may reflect a more sophisticated and empathy-related reading of the observed body expression "from the inside" (Avenanti, Candidi, & Urgesi, 2013b;Avenanti & Urgesi, 2011;Gazzola et al, 2006;Rizzolatti & Sinigaglia, 2010).…”
Section: Introductionmentioning
confidence: 88%
“…We believe that this is an inaccurate reading of the neuroscientific work on mirror neurons: for a neuroscientist, stating that mirror neurons could contribute to social cognition and thus endow animals with fitness advantages does not automatically translate into suggesting that humans and monkeys are hardwired to have mirror neurons and that learning must only have a minimal impact on mirror neurons. What neuroscientists mean is that if one were to disturb the function of mirror neurons, this would lead to impairments in social cognition and a growing body of evidence now exists to support this claim [48]. Such a claim is compatible with the genome undergoing selective pressure to facilitate mirror neurons, but it does not imply that this selection has already generated a strong genetic encoding or that the genetic influence takes the form of pre-wiring at birth.…”
Section: (D) Alternative Accountsmentioning
confidence: 99%